Vacuum Testing of a Miniaturized Switch Mode Amplifier Powering an Electrothermal Plasma Micro-Thruster - Charles, Christine; Liang, Wei; Raymond, Luke; Rivas-Davila, Juan; Boswell, Roderick W. (Frontiers in Physics, 2017)
A structurally supportive miniaturised low-weight (150 g) radiofrequency switch mode amplifier developed to power the small diameter Pocket Rocket electrothermal plasma micro-thruster called MiniPR is tested in vacuum conditions representative of space to demonstrate its suitability for use on nano-satellites such as `CubeSats'. Argon plasma characterisation is carried out by measuring the optical emission signal seen through the plenum window versus frequency (12.8-13.8 MHz) and the plenum cavity pressure increase (indicative of thrust generation from volumetric gas heating in the plasma cavity) versus power (1-15 Watts) with the amplifier operating at atmospheric pressure and a constant flow rate of 20 sccm. Vacuum testing is subsequently performed by measuring the operational frequency range of the amplifier as a function of gas flow rate. The switch mode amplifier design is finely tuned to the input impedance of the thruster (16 pF) to provide a power efficiency of 88 % at the resonant frequency and a direct feed to a low-loss (10 %) impedance matching network. This system provides successful plasma coupling at 1.54 Watts for all investigated flow rates (10-130 sccm) for cryogenic pumping speeds of the order of 6000 l.s^-1 and a vacuum pressure of the order of 2x10^-5 Torr during operation. Interestingly, the frequency bandwidth for which a plasma can be coupled increases from 0.04 to 0.4 MHz when the gas flow rate is increased, probably as a result of changes in the plasma impedance.